PURCHASE INTENT IN E-COMMERCE: THE IMPACT OF SCARCITY AND DISCOUNT VOUCHER STRATEGIES ON SHOPEE USERS IN BENGKULU CITY - Delfi Novtiara; Meilaty Finthariasari (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2026)
This study examines the effect of Scarcity and Voucher Discounts on Purchase Intent among Shopee users in Bengkulu City. Despite significant e-commerce growth globally, the conversion rate from intent to actual transaction remains relatively low, indicating a critical gap in promotional effectiveness in regional markets. This study discusses the lack of empirical evidence regarding the simultaneous impact of scarcity and discount vouchers, especially in developing a digital context such as Bengkulu. Using a quantitative descriptive approach, data was collected from 110 active Shopee users aged 18-35 years through purposive sampling. The analysis used multiple linear regression using SPSS software. The results show that Voucher Scarcity and Discount positively and significantly affect Purchase Intent individually. Discount vouchers were found to be the dominant variable that influenced consumer behavior. Simultaneously, these two variables explain 68.7% of the variance of Purchase Intent. These findings suggest that integrating scarcity strategies with discount vouchers can effectively increase consumer purchase intent. This study contributes to the digital marketing literature and offers practical implications for MSMEs and platform managers in optimizing promotional strategies.